El microcrédito y el crecimiento económico de los comerciantes del mercado Señor de los Milagros de Contamana, 2021 - Ramos Armas, Istuan Steven (2022)
In the investigation it had as objective; determine the relationship between microcredit and the economic growth of the merchants of the Señor de los Milagros de Contamana Market, 2021. Opting for a descriptive-correlational type of research and a non-experimental design. Where the survey was used as a technique and the questionnaire as an instrument. Concluding that microcredit maintains a positive and considerable relationship of 0.870 with the economic growth of merchants, at the same time, it was determined that the dimensions credit delivery (rs=0.842) and credit repayment (rs=0.798) maintain a positive and considerable relationship with economic growth, however, the creditor dimension of credit (rs=0.704) maintains a positive and medium relationship.